Prospek Pembangunan Area Percontohan Smart City Polder Sangatta Utara Kabupaten Kutai Timur - Pratiwi, Diana Nur; Budiman, Budiman; Syarifuddin, Tengku Imam; Jumansyah, Jumansyah (Administratio, 2021)
This research aims to identify and evaluate the prospect of creating a pilot smart city area in North Sangatta Polder, Kutai Regency, in order to increase the development of a technology-based smart city. In this analysis, data collection techniques were obtained through the use of purposive sampling and accidental sampling techniques. The data analysis used in this study is a qualitative review that aims to explain in detail the growth prospects of East Kutai Regency, which is a smart city pilot area in North Sangatta. The results showed, for the North Sangatta Polder Research, East Kutai Regency, the prospect of developing a Smart City pilot area. Increase tourist visits outside the region, improve the regional economy, promote access to information for the community, increase technology understanding, create jobs, attract tourists by building tourism in North Sangatta Polder with the promotion of tourist objects that involve the government, private sector, and the community in management, growth, construction, and development of tourist objects.